Prabowo’ Conversational Implicatures in Mata Najwa’s Program - Dwi Santoso; Rahmawati (CV. Creative Tugu Pena, 2024)
The Republic of Indonesia's potential presidential candidates first got together on September 19, 2023, at Mata Najwa's